A GLOBAL PERSPECTIVE OF VEHICULAR EMISSION CONTROL POLICY AND PRACTICES: AN INTERFACE WITH KATHMANDU VALLEY CASE, NEPAL - Das, Bhupendra; Bhave, Prakash V.; Puppala, Siva Praveen; Byanju, Rejina M. (Journal of Institute of Science and Technology, 2019)
Transport sector is growing most rapidly around the world in line with the urban and socio-economic growth, which is contributing to severe air pollution. Air pollution has been of much concern mainly due to air quality, human exposure, public health, climate change, and visibility reduction. At present, in the media and policy arena, significant attention is given to the transport air pollution and its effect. Although most of the developed countries established vehicular emission control practices, it is very primitive in the developing countries including Nepal. This paper highlights global policies/legislations that have been practiced for emissions control from high emitting vehicles based on the available literature. The insights and lessons based information presented in this paper will add value to the policy makers for creating strong policy packages of air quality management for Kathmandu valley including other parts of Nepal.